Icariin Treatment Protects Against Gentamicin-Induced Ototoxicity via Activation of the AMPK-SIRT3 Pathway - Hu, Yue; Ma, Xiulan (Frontiers in Pharmacology, 2021)
Ototoxicity is a serious health problem that greatly affects millions of people worldwide. This condition is caused by the entry of aminoglycosides into auditory hair cells, subsequently inducing reactive oxygen species (ROS) production and accumulation. Several strategies have been adopted to overcome irreversible ROS-induced hair cell loss in mammals. In recent years, icariin, a major active component of the traditional herb Epimedium, has been widely studied and revealed to have antioxidant, anti-inflammatory, and anti-apoptotic properties. In this study, we found that icariin pretreatment improved the survival rate of gentamicin-treated House Ear Institute-Organ of Corti 1 (HEI-OC1) cells and cochlear explants. Icariin remarkably suppressed HEI-OC1 cell apoptosis and inhibited ROS production in cells. Notably, icariin upregulated PGC-1α (SIRT3 promoter) and SIRT3 expression in HEI-OC1 cells. In addition, SIRT3 inhibition significantly attenuated the anti-apoptotic effect of icariin. We also found that icariin can increase AMPK phosphorylation. Further studies showed that inhibition of SIRT3 activity had no significant effect on AMPK phosphorylation. Furthermore, the AMPK inhibitor compound C significantly suppressed SIRT3 expression, meaning that AMPK, as an upstream molecule, regulates SIRT3 expression. Meanwhile, inhibition of AMPK activity significantly reduced the protective effect of icariin on gentamicin ototoxicity. Based on these results, icariin exerts its protective effect on gentamicin-induced ototoxicity via activation of the AMPK-SIRT3 signaling pathway, thus providing a new strategy for treating ototoxicity caused by aminoglycoside antibiotics.